Perancangan Interior Pusat Fasilitas Komunitas Bonek di Surabaya - Michael Liansyah (Intra, 2016)
The design of Facilities Center for Bonek Community in Surabaya is aimed to raise the positive image of Bonek. The place will be a Bonek Community Center which form a social network that connects between Bonek community, other community, Persebaya club, Surabaya’s people, and visitors from outside Surabaya. So by the existence of this facility center that facilitate and lifting positive activities that done by Bonek community, can change people's perception towards this community become better and more positive. This design accommodates all information about the history of Persebaya club and Bonek community itself. The information packaged in informative, educative, and recreational way so the visitors can get new experience and new positive mindset towards Bonek community. Bonek Community Information Center has some facilities such as information center, gathering space, food corner, temporary exhibition area, radio broadcast room, merchandise store, graphic workshop, murals workshop, and press conference area.